EFEKTIVITAS PENGGUNAAN KERJA KELOMPOK UNTUK MENINGKATKAN HASIL BELAJAR PEMBUATAN BUSANA CUSTOM MADE DI SMK NEGERI 2 SELONG LOMBOK TIMUR - Kamardikaningsih, Siti Latifah (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The aim of this research was; to determine the effectiveness of using group work to improve learning outcomes for making Custom Made Clothing at SMK Negeri 2 Selong. After conducting research and analysis, this research shows the results that; with group work: a) Can encourage the growth and development of students' critical and analytical thinking potential optimally, b) Train students to be active, creative, and critical in dealing with every problem, c) Encouraging the growth of an attitude of tolerance, willing to listen and respecting the opinions of others, d) Encouraging the growth of democracy among students, e) Training students to increase the exchange of opinions objectively, rationally and systematically in arguing in order to find something true in cooperation between group members , and f) Encouraging the growth of the courage to express students' opinions openly, seventh trains to always be able to be independent in dealing with every problem, eighth trains student leadership, ninth broadens students' horizons through exchanging information, opinions and experiences between them, tenth was a forum for effective for teaching and learning activities. Thus, it can be concluded that " Group Work was Effective to Improve Student Learning Outcomes in Making Custom Fashion Clothing at SMK Negeri 2 Selong, East Lombok Regency.